195k views
3 votes
What is the factor of

{x}^(2) - 6x - 27


User Ayaz Pasha
by
5.2k points

2 Answers

1 vote

Answer:

9 is correct answer

Explanation:


{x}^(2) - 6x - 27 \\ = {x}^(2) - 9x + 3x - 27 \\ = x(x - 9) + 3(x - 9) \\ = (x + 3)(x - 9)

x=9

User SaurabhSharma
by
4.7k points
6 votes

Answer:

(x - 9)(x + 3)

Explanation:

Given

x² - 6x - 27

Consider the factors of the constant term (- 27) which sum to give the coefficient of the x- term (- 6)

The factors are - 9 and + 3, since

- 9 × 3 = - 27 and - 9 + 3 = - 6, thus

x² - 6x - 27 = (x - 9)(x + 3)

User Erlin
by
5.1k points